نظام إدارة الطاقة الإيزو 50001 و الكفاءة الطاقوية - دراسة حالة - زين الدين قنادزية (My University, 2022)
This study aimed to highlight the economic, energy and environmental gains from localizing the ISO 50001 energy management system in a group of well-known international institutions. To accomplish this study, the case study method was relied upon, in addition to the internal files of the institutions under study related to ISO 50001 that are available on the Internet. This study reached the following results:This system has achieved several gains for these institutions at all levels of energy, material and environment, as the quantities of energy consumption have decreased significantly, energy costs have decreased by very significant rates, and greenhouse gas emissions have also decreased as a natural result of the decline in energy consumption, which prevented the institutions from paying huge sums of money to the public authorities in the form of fees It was also noted that the recovery period for the localization of energy management system costs was short in all the institutions under study .................................................... هدفت هذه الد ا رسة لإبراز المكاسب الاقتصادية والطاقوية والبيئية من توطين عام ادارة الطاقة الايزو 50001 في مجموعة من المؤسدات العالمية المعروفة . لإنجاز هذه الدراسة تم الاعتماد على منهج دراسة الحالة الى جانب الملفات الداخلية للمؤسسات محل الدارسة المتعلقة بالايزو 50001